PELATIHAN STRATEGI DIGITAL MARKETING EFEKTIF UNTUK PELAKU UMKM DI DESA SENGGIGI, KABUPATEN LOMBOK BARAT - Abdurrahman, Abdurrahman; Dakwah, Muhammad Mujahid; Girsang, Zefanya Andryan; Muhtarom, Zamroni Alpian; Rinuastuti, Baiq Handayani; Roodhi, Mohammad Najib; Mulyono, Lalu Edy Herman; Ibrahim, Isra Dewi Kuntary (Universitas Mataram, 2025)
Senggigi Village is one of the tourist villages with abundant natural resources. It is located in Batulayar Subdistrict, West Lombok Regency, West Nusa Tenggara Province. Senggigi Village is known for its beautiful beaches and the hospitality of its people. In addition, Senggigi Village has local products that support tourism activities in the village as souvenirs for tourists visiting Senggigi. To enhance the potential of local businesses in Senggigi Village, it is necessary to provide guidance to SMEs with the aim of offering effective digital marketing strategy training for local SMEs. This training can improve SMEs' ability to optimize the use of social media and e-commerce as marketing tools for their products. The activity methods include initial observation, focus group discussions (FGD), training, hands-on practice, and post-training guidance. The results of this activity demonstrate an increase in participants' understanding and skills in creating promotional content, managing business social media accounts, and developing digital marketing strategies tailored to their respective products using the Marketing Decision Support (MDS) approach. The conclusion of this activity is that digital marketing training provides tangible contributions to enhancing the business capacity of SME operators and can serve as a model for sustainable community service.